Pericles on stage political comedy in Aristophanes' early plays - Vickers, Michael J. 1943- (Univ. of Texas Press, 1997)
According to Vickers, the plays of Aristophanes - far from being nonpolitical - actually allow us to gauge the reaction of the Athenian public to the events which occured in the years following Pericles' death in 429 B.C., to the struggle for the political succession, and to the problems presented by Alcibiades' gradual emergence as one of the most powerful figures in the state. This view of Aristophanes reaffirms the central role of allegory in his work and challenges all students of ancient Greece to rethink long-held assumptions about this important playwright
Keywords: Aristophane <0445?-0386? av. J.-C.> - Critique et interprétation; Périclès <0495?-0429 av. J.-C.> - Critique et interprétation; Pericles <ca. 495-429 B.C> -- In literature; Aristophanes -- v445-v385; Perikles -- ca. 495/490 v. Chr.-429 v. Chr.; Geschichte 479 v. Chr.-431 v. Chr.; Perikles; Comédie grecque - Histoire et critique; Komedies; Politieke situatie; Politik; Politique et littérature - Athènes (Grèce); Politische Situation; Aristophanes -- Political and social views; Greek drama (Comedy) -- History and criticism; Political plays, Greek -- History and criticism; Politics and literature -- Greece -- Athens; Politisches Theater; Komödie; Athènes (Grèce) - Politique et gouvernement; Griechenland; Athens (Greece) -- Politics and government; Griechenland -- Altertum